Montmorillonite modified with copper ions: Efficient adsorbent for aflatoxin B1 - Daković Aleksandra; Sekulić Živko; Rottinghaus Georg E.; Matijašević Srđan; Milićević Sonja; Stojanović Ana (Veterinarski Glasnik, 2008)
In this paper, the results of preparation of material for adsorption of aflatoxin B1, based on modification of montmorillonite with copper ions (Cu-MONT), are presented. The bentonite clay from Sokolac deposit (Šipovo, Bosnia) was used as the starting raw material. After modification of concentrate of montmorillonite (MONT) with copper, the content of copper in Cu-MONT, was 2.65%. It was shown that MONT, as well as the Cu-MONT were efficient in adsorption of aflatoxin B1, at different mass ratios of adsorbent : toxin, and at different pH values. It was determined that for MONT, at the mass ratio adsorbent : toxin = 5000 : 1, aflatoxin B1 adsorption index was 100% at pH 3, 98% at pH 7 and 96% at pH 9. For Cu-MONT, at the same mass ratio, the following aflatoxin B1 adsorption indexes were achieved: 98% at pH 3, 98% at pH 7 and 96% at pH 9. No differences in adsorption of this toxin by both montmorillonites with decreasing the mass ratio of adsorbent : toxin (250 : 1) were observed. That means that ion exchange of inorganic cations in montmorillonite with copper ions did not cause any changes in aflatoxin B1 adsorption, at pH 3, as well as at pH 7 and 9. It was also noticed that adsorption of aflatoxin B1 by MONT and Cu-MONT was not pH dependent.